2013
DOI: 10.1111/cei.12051
|View full text |Cite
|
Sign up to set email alerts
|

Human T cells depend on functional calcineurin, tumour necrosis factor-α and CD80/CD86 for expansion and activation in mice

Abstract: + T cells alone were sufficient for expansion and required for disease development; in contrast, CD4 + T cells alone expanded but did not induce acute disease and, rather, exerted regulatory capacity through CD25 + CD4 + T cells. Using various anti-inflammatory compounds, we demonstrated that several T cell-activation pathways controlled T cell expansion and disease development, including calcineurin-, tumour necrosis factor-a and co-stimulatory signalling via the CD80/CD86 pathway, indicating the diverse mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 47 publications
5
43
0
Order By: Relevance
“…On the other hand, transplantation of Th17-polarized cells alone (not combined with PBMCs) revealed that Th17 cells did not generate lethal xGVHD by themselves, nor did Th0 and Th1 cells. This finding is in accordance with previous reports in NSG mice showing that purified CD4 + T cells only mediated delayed and mild xGVHD [23,30,33,35,51]. Thus, although Th17 cells were not sufficient to individually induce lethal xGVHD, our experiments using Th17 cotransfer with PBMCs demonstrated that these cells nevertheless could exacerbate the disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, transplantation of Th17-polarized cells alone (not combined with PBMCs) revealed that Th17 cells did not generate lethal xGVHD by themselves, nor did Th0 and Th1 cells. This finding is in accordance with previous reports in NSG mice showing that purified CD4 + T cells only mediated delayed and mild xGVHD [23,30,33,35,51]. Thus, although Th17 cells were not sufficient to individually induce lethal xGVHD, our experiments using Th17 cotransfer with PBMCs demonstrated that these cells nevertheless could exacerbate the disease.…”
Section: Discussionsupporting
confidence: 93%
“…Over the past several decades, humanized murine models of xenogeneic GVHD (xGVHD) have been developed via the injection of human peripheral blood mononuclear cells (PBMCs) into severely immunodeficient NOD/Shi-scid IL2rg-null (NOG) or NOD/LtSz-scid IL2rg-null (NSG) mice [23][24][25][26][27][28][29][30][31][32]. These models are T cell dependent, and main triggers of T cell activation and expansion are xenogeneic MHC (H-2) class I and class II molecules [23,30,33,34] and xenogeneic costimulatory signals [27,35]. Previous studies have demonstrated a crucial interplay between CD4 + and CD8 + T cells during xGVHD [23,35]; however, the concrete role of individual T cell subsets has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prior report shows that CD4 + T cells in humanized mice can exhibit regulatory capacity 51 and raises the possibility that stimulation of Treg by MSC therapy could alter bone marrow destruction after injury. We www.nature.com/scientificreports/ therefore examined T lymphocyte frequencies in various organs.…”
Section: Resultsmentioning
confidence: 99%
“…The NSG, NRG, and NOG lines all natively express murine major histocompatibility complex (MHC), and in the presence of human T-cells restricted by human leukocyte antigen (HLA), such as in the PBMC and BLT models, a xeno-MHC mismatch occurs that drives GvHD development (50). CD8 + T-cells mediate GvHD in PBMC humanized mice, while CD4 + T-cells alone are not sufficient to cause this disease (51). The HSC model relies on human T-cell selection and development in the murine thymus, resulting in T-cells likely restricted by murine MHC (50,52,53).…”
Section: Development Of Humanized Mouse Models That Mitigate Gvhdmentioning
confidence: 99%